Community Anxiety During Pandemi Covid-19 at Medan Selayang District - Jagentar Pane; Lindawati Simorangkir; Friska Sri Handayani Br Ginting; Amando Sinaga (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Covid-19 (`Corona Virus Diseases) is affecting lives all over the world. Information on the spread of COVID-19 is continuously reported in Indonesia through print, electronic, and social media and is declared a pandemic. This research is very important considering the number of Covid-19 sufferers is increasing every day so that people are not ready to face it both physically and psychologically. One of the psychological conditions experienced by society today is anxiety which has an impact on the decrease in the body's immune system. The purpose of this study was to identify the level of public anxiety during the COVID-19 pandemic in Medan Selayang District. This type of research is descriptive with a total sample of 79 people. Data collection using the Hanifah 2020 questionnaire with a cronbach alpha value = 0.801. Sampling technique with Simple Random Sampling. The results of the study the majority of respondents had moderate levels of anxiety as many as 43 people (54.4%), mild as many as 24 people (30.4%), severe as many as 11 people (13.9%), and panic as many as 1 person (1.3 %).